2015
DOI: 10.1155/2015/785461
|View full text |Cite
|
Sign up to set email alerts
|

CD73 Predicts Favorable Prognosis in Patients with Nonmuscle-Invasive Urothelial Bladder Cancer

Abstract: Aims. CD73 is a membrane associated 5′-ectonucleotidase that has been proposed as prognostic biomarker in various solid tumors. The aim of this study is to evaluate CD73 expression in a cohort of patients with primary bladder cancer in regard to its association with clinicopathological features and disease course. Methods. Tissue samples from 174 patients with a primary urothelial carcinoma were immunohistochemically assessed on a tissue microarray. Associations between CD73 expression and retrospectively obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 56 publications
2
23
0
Order By: Relevance
“…For epithelial ovarian carcinomas, Oh et al found CD73-high expression predicted better prognosis, lower stage, and higher degree of differentiation [ 22 ]. The similar result has also been reported in nonmuscle-invasive urothelial bladder cancer [ 23 ]. Nevertheless, other researches in colorectal, gastric, gallbladder, prostate and triple negative breast cancer, proved CD73 was an unfavorable prognostic marker [ 2 , 5 , 24 , 25 ].…”
Section: Introductionsupporting
confidence: 89%
“…For epithelial ovarian carcinomas, Oh et al found CD73-high expression predicted better prognosis, lower stage, and higher degree of differentiation [ 22 ]. The similar result has also been reported in nonmuscle-invasive urothelial bladder cancer [ 23 ]. Nevertheless, other researches in colorectal, gastric, gallbladder, prostate and triple negative breast cancer, proved CD73 was an unfavorable prognostic marker [ 2 , 5 , 24 , 25 ].…”
Section: Introductionsupporting
confidence: 89%
“…Accordingly, studies that reconcile tissue-and cell-specific roles for CD73 in normal GI tissues may help better understand CD73 in GI cancers (179,180). Similar to endometrial cancer (175), CD73 is downregulated in cancer cells of bladder and prostate tumors and associates with poor prognosis (181,182). The role of CD73 in bladder and prostate epithelium is unknown.…”
Section: Liver Cancermentioning
confidence: 99%
“…High CD73 expression associates with lower stage and grade, less adjacent carcinoma in situ, lower proliferation index, and is a predictor of better outcome in patients with nonmuscle-invasive bladder cancer. 16 CD73 expression is associated with both good 17 and poor 7 prognosis in breast cancer. Down-regulation of CD73 in endometrial carcinoma occurs in the carcinoma cells.…”
Section: Cd73 Is Not Always Upregulated In Cancer and Is Not Always Amentioning
confidence: 99%